Development of Management Structure of Timber Industry Enterprises in the Republic of Belarus - S. I. Baranovsky; A. N. Valko (Наука и техника)
The paper considers basic problems concerning development of a timber industry complex in the Republic of Belarus. Comparative analysis of «Bellesbumprom» Concern activity and timber industry complex as a whole is given in the paper. As one of ways pertaining to reformation of timber industry complex and management development it is proposed to establish holding companies